Motives for building relationships between Generation Z customers and businesses via YouTube in Poland and Great Britain - Ławińska, Olga; Korombel, Anna (Journal of Management and Financial Sciences, 2025)
The aim of the article was to identify and assess the motives for building relationships between Generation Z customers and businesses via YouTube in Poland and Great Britain. The study of these motives is part of the broader research conducted by the authors among students in Poland and Great Britain in 2023. The study used a survey method with the CAWI technique. Descriptive statistical measures were used to analyze the research material. The results show that before using a service or purchasing a product of a specific company, respondents often searched for its account on YouTube. The most important benefits associated with following the company on YouTube by respondents in both countries surveyed were also identified. The relationship between the benefits analyzed and the respondent’s gender and place of residence was also examined.